Hydrolysis-Engineered Robust Porous Micron Silicon Anode for High-Energy Lithium-Ion Batteries - Liu, Mili; Liu, Jiangwen; Jia, Yunqi; Li, Chen; Zhang, Anwei; Hu, Renzong; Liu, Jun; Wang, Chengyun; Ma, Longtao; Ouyang, Liuzhang (Nano-Micro Letters, 2025)
Micro-silicon (Si) anode that features high theoretical capacity and fine tap density is ideal for energy-dense lithium-ion batteries. However, the substantial localized mechanical strain caused by the large volume expansion often results in electrode disintegration and capacity loss. Herein, a microporous Si anode with the SiOx/C layer functionalized all-surface and high tap density (~ 0.65 g cm⁻3) is developed by the hydrolysis-driven strategy that avoids the common use of corrosive etchants and toxic siloxane reagents. The functionalized inner pore with superior structural stability can effectively alleviate the volume change and enhance the electrolyte contact. Simultaneously, the outer particle surface forms a continuous network that prevents electrolyte parasitic decomposition, disperses the interface stress of Si matrix and facilitates electron/ion transport. As a result, the micron-sized Si anode shows only ~ 9.94 GPa average stress at full lithiation state and delivers an impressive capacity of 901.1 mAh g⁻1 after 500 cycles at 1 A g⁻1. It also performs excellent rate performance of 1123.0 mAh g⁻1 at 5 A g⁻1 and 850.4 at 8 A g⁻1, far exceeding most of reported literatures. Furthermore, when paired with a commercial LiNi0.8Co0.1Mn0.1O2, the pouch cell demonstrates high capacity and desirable cyclic performance. Highlights: 1 There is a novel “hydrolysis-driven synthesis” approach for the preparation of a dual-surface functionalized micron-sized Si anode with a SiOx/C layer. 2 The functionalized inner pores and dual-functional SiOx/C layer synergistically alleviate volume change of Si lithiation, minimize stress concentration and improve electrochemical reaction kinetics. 3 The optimized micron-Si anode performs impressive lifespan, excellent high rate capacity and outstanding stack cell volumetric energy density.